2018
DOI: 10.1016/j.rmed.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performances of the Xpert MTB/RIF in Brazil

Abstract: Xpert is sensitive and specific in the Brasilian settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
7
1
3
Order By: Relevance
“…There is still a lack of information about Xpert performance under programmatic conditions in Brazil despite its regular use in many high-burden cities since 2014 [5]. Recent studies in Brazil showed that the use of the Xpert MTB/RIF increased detection of TB cases among paucibacillary patients [14], adolescents [15] and the HIV-positive population [16].…”
Section: Discussionmentioning
confidence: 99%
“…There is still a lack of information about Xpert performance under programmatic conditions in Brazil despite its regular use in many high-burden cities since 2014 [5]. Recent studies in Brazil showed that the use of the Xpert MTB/RIF increased detection of TB cases among paucibacillary patients [14], adolescents [15] and the HIV-positive population [16].…”
Section: Discussionmentioning
confidence: 99%
“…Models predict that elimination of TB can be reached within the next few decades and can discern what the relevant contribution of a new vaccine, new (shorter and better tolerated) regimens to manage TB and LTBI and a new point of care diagnostic test would be [32,33]. Diagnosis and treatment of LTBI outperforms other interventions in these scenarios.…”
Section: The End Tb Strategymentioning
confidence: 99%
“…Recent evidence suggests that correct treatment is extremely effective in rendering the patient rapidly non-infectious. Today, the availability of rapid diagnostic methods allows us to identify, within a few hours, whether the strain is susceptible or resistant to drugs and, therefore, enables appropriate treatment accordingly [32,33,[35][36][37]. Unfortunately, the practice of treating patients with the standard regimen for new cases ("blindly" as far as drug resistance is concerned) and considering drug susceptibility testing only when treatment failure occurs is still common in many settings [93].…”
Section: The End Tb Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Both articles emphasize that is essential to determine the effect of the Xpert MTB/RIF assay on the diagnosis of tuberculosis under programmatic conditions in Brazil. (11) Improving the coverage and quality of diagnosis for individuals infected with drug-resistant tuberculosis is also relevant. In a cohort study conducted at a referral center for tuberculosis in the state of São Paulo, Brazil, between 2006 and 2010, (7) the authors found that early detection of infection with a drug-resistant strain of M. tuberculosis was associated with higher cure rates in patients without comorbidities and in patients with a higher body weight at the beginning of treatment (in comparison with the cure rates observed for those without comorbidities and for those with a lower body weight at the beginning of treatment).…”
mentioning
confidence: 99%